NOX66 as Monotherapy, and in Combination With Carboplatin, in Patients With Refractory Solid Tumors: Phase Ia/b Study - Koba Kiknavelidze, PhD; Mikheil Shavdia, PhD; Nana Chikhladze, PhD; Lia Abshilava, PhD; Marinella Messina, PhD; Gisela Mautner, MD, PhD; Graham Kelly, PhD (Elsevier, 2021)
ABSTRACT: Background: Although oral and intravenous forms of idronoxil have been well tolerated, the safety of NOX66, with idronoxil formulated as a rectal suppository, is not known. This Phase Ia/b clinical study (protocol No. NOX66-001A), known as Chemotherapy Enhancement Program-1, is the first to assess NOX66 in patients with refractory solid tumors. Objective: The study aimed to determine the safety profile of NOX66 both as a monotherapy and in combination with carboplatin, and to evaluate whether or not NOX66 has a meaningful anticancer effect when combined with carboplatin in this patient population. Methods: Chemotherapy Enhancement Program-1 was a multicenter, open-label, nonrandomized, 2-dose cohort study of NOX66 as monotherapy (Phase Ia) and in combination with carboplatin (Phase Ib). Patients with refractory solid tumors who had stopped responding to standard treatments were eligible to participate. Twenty patients were screened and 19 enrolled in the study. They were divided into 2 groups: cohort 1 (n = 8) received 1 suppository daily (400 mg) and cohort 2 (n = 11) received 2 suppositories daily (800 mg) for 14 consecutive days followed by 7 days of rest. Patients who completed Phase Ia without significant toxicity continued to Phase Ib, where NOX66 was combined with carboplatin for up to 6x 28-day treatment cycles, with low-dose carboplatin (600 mg) for cycles 1B through 3B and standard dose carboplatin (900 mg) for cycles 4B through 6B. The main outcomes assessed were safety (n = 18) and efficacy signals (n = 14). Results: NOX66 generally was well tolerated at 400 mg and 800 mg, both as monotherapy and in combination with carboplatin in patients with refractory solid tumors. The safety profile was consistent for oncology patients, with 77.8% experiencing at least 1 treatment-emergent adverse event. The most common adverse events were blood and lymphatic system disorders (44.4%), with only anemia considered as possibly related to NOX66. Although the study was primarily designed to assess safety and tolerability, the efficacy measurements demonstrated that most patients had stable disease or better by study end. Conclusions: The favorable safety profile of NOX66 provides reassurance to justify continuation of clinical research. The efficacy findings are encouraging in terms of the chemosensitizing potential of NOX66 in refractory solid tumors. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)